Do the metrics matter? An experimental investigation of Instagram influencer effects on mood and body dissatisfaction. (March 2021) - Lowe-Calverley, Emily; Grieve, Rachel
Highlights: Idealised influencer images lead to greater negative mood. Idealised influencer images lead to greater body dissatisfaction. No differences found between idealised images with high vs. low popularity metrics. Abstract: Instagram is saturated with content from 'influencers', users who create high-quality idealised content, attain celebrity-level following, and often leverage their popularity to earn money through brand partnership/promotion. Although existing literature generally indicates the negative impact of idealised Instagram imagery on female psychological wellbeing, influencer imagery has yet to receive thorough attention. We investigated the impact of high versus low popularity influencer images on mood and body dissatisfaction. Adult women ( N = 111, aged 17–40) were randomly allocated to one of three groups: either (1) the influencer-high group (idealised imagery alongside high 'like'/follow metrics); (2) the influencer-low group (the same idealised imagery adjusted for low popularity metrics); or (3) a nature control group with matched low-popularity metrics. Results revealed significantly higher negative mood and body dissatisfaction within the two influencer imagery groups compared with the control group. Interestingly, comparisons revealed no significant differences between the influencer-high and influencer-low groups on mood and body dissatisfaction. The findings suggest that users should be aware of the potentially negative impacts of viewing idealised influencer imagery, regardless of whether the content is high or low in popularity.